Free flaps for reconstruction of soft tissue defects in lower extremity: A meta-analysis on microsurgical outcome and safety - Xiong, Lingyun; Kremer, Thomas; Hernekamp, Jochen-Frederick; Harhaus-Wähner, Leila; Kneser, Ulrich; Hirche, Christoph (Microsurgery, 2016)
Background Microsurgical free flaps for reconstruction of soft tissue defects in lower extremity have evolved into a reliable procedure over last decades; however, there lacked high level of evidence. Methods A systematic literature research was performed including studies between 2000 and 2014 in English, German, and Chinese (PubMed, EMBASE). Publications were selected applying inclusion/exclusion criteria. Postoperative complications were statistically analyzed with metaprop command of R GUI 3.0.1. Results Alltogether 30 articles overlooking 1,397 free flaps were included. The rate of total flap loss was 6.0% (95% confidence interval [CI] = 4.0%-8.0%, PQ (P values of Q statistics) = 0.03); the thrombosis rate was 6.0% (95% CI = 4.0%-9.0%, PQ = 0.01); the hematoma rate was 4.0% (95% CI = 3.0%-5.0%, PQ = 0.79); the partial necrosis rate was 6.0% (95% CI = 4.0%-10.0%, PQ < 0.01); the early infection rate was 4.0% (95% CI = 2.0%-6.0%, PQ = 0.03), and the dehiscence rate was 3.0% (95% CI = 2.0%-5.0%, PQ = 0.12). Reconstruction for diabetic foot may be not associated with a significant increase of procedural risk (Total flap loss rate = 6%, 95% CI = 3.0%-9.0%, PQ = 0.44). Conclusions Microsurgical reconstruction of soft tissue defects in the lower extremity reconstruction could be regarded safe and reliable. A standardization of report of perioperative parameters and clinical outcomes is needed.